2021
DOI: 10.3390/biom11101400
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Reduction of Calcium Oscillations in Adipose-Derived Stem Cells Differentiating towards Adipogenic and Osteogenic Lineage

Abstract: Adipose-derived mesenchymal stromal cells (ASCs) are multipotent stem cells which can differentiate into various cell types, including osteocytes and adipocytes. Due to their ease of harvesting, multipotency, and low tumorigenicity, they are a prime candidate for the development of novel interventional approaches in regenerative medicine. ASCs exhibit slow, spontaneous Ca2+ oscillations and the manipulation of Ca2+ signalling via electrical stimulation was proposed as a potential route for promoting their diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This seems to reflect a more extensive deposition of calcium phosphate nodules for donor 1, consistently with the higher osteogenesis extension shown by ALP levels. Indeed, an increase in total calcium content (including insoluble forms at pH 7) has been reported for hAMSCs undergoing osteogenic differentiation [ 58 ], while calcium stagnation has been interpreted as reflecting stable intracellular calcium levels [ 60 ], thus corroborating the lower mineralization extension characterizing donor 2.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This seems to reflect a more extensive deposition of calcium phosphate nodules for donor 1, consistently with the higher osteogenesis extension shown by ALP levels. Indeed, an increase in total calcium content (including insoluble forms at pH 7) has been reported for hAMSCs undergoing osteogenic differentiation [ 58 ], while calcium stagnation has been interpreted as reflecting stable intracellular calcium levels [ 60 ], thus corroborating the lower mineralization extension characterizing donor 2.…”
Section: Resultsmentioning
confidence: 91%
“…Total calcium quantification ( Figure S1D ) informs on (i) intracellular calcium, (ii) free calcium ions in the extracellular matrix (ECM), and (iii) calcium ions associated with insoluble mineral deposition (e.g., calcium phosphates). The normalized overall calcium content profile ( Figure S1D ) showed relatively higher values at day 7 for basal conditions for both donors, possibly reflecting high intracellular calcium content [ 60 ]. While calcium levels decreased in basal conditions throughout days 7 to 21 for both donors, in osteogenic conditions a significant increase in calcium content was observed for donor 1 at day 21, while a smaller non-significant increase was noted for donor 2.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with this hypothesis, flecainide decreased the frequency of Ca 2+ sparks and normalised the Ca 2+ transients elicited by membrane depolarization in inducible pluripotent stem cell-derived cardiomyocytes isolated from an ACM patient bearing a mutation in the DSC2 gene [ 49 ]. It has long been known that oscillations in intracellular Ca 2+ concentration ([Ca 2+ ] i ) regulate MSC differentiation into a variety of cells belonging to multiple lineages [ 50 , 51 , 52 ]. Moreover, a recent study carried out in our laboratory showed that intracellular Ca 2+ oscillations drive proliferation in C-hMSCs [ 53 ].…”
Section: The Rationale For Using Flecainide To Treat Ca 2+ ...mentioning
confidence: 99%
“…Spontaneous intracellular Ca 2+ oscillations have been described not only in BM-hMSCs [ 54 , 83 , 84 ] but also also in human adipose tissue-derived MSCs (AD-hMSCs) [ 51 , 85 ]. Intracellular Ca 2+ oscillations regulate stem cell differentiation by stimulating the expression of genes that control cellular fate and silencing those that are required for self-renewal [ 52 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Intracellular Ca 2+ Oscillations Regulate...mentioning
confidence: 99%
“…In their study, Torre at al. showed that undifferentiated ASCs and cells that differentiate towards the osteogenic and adipogenic fates are characterised by very distinct calcium oscillation patterns [15]. Notably, this methodology can be exploited as a non-invasive technique for assessing ASC differentiation in vitro.…”
mentioning
confidence: 99%